“Pandemic” lessons on constraints, enablers, and preservice teachers’ training (mis)alignment in physical education teacher education - Cláudio Farias; João Martins FMH Martins; Javier Fernandez-Rio (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: the COVID-19 pandemic significantly affected all spheres of social life, particularly in education (schools and higher education). It is particularly important to study the specific context of physical education preservice teachers’ professional training, as they serve as a critical vehicle for the renewal of teaching practices in schools.